Analisis Attraction, Amenities, Accessability dan Ancillary Dalam Penawaran Produk Ekowisata di Pantai Klayar - Edhy Purwanto, Firdiansyah Nugroho; Agus Subianto; Herman (Journal Of Accounting and Business, 2023)
Klayar Beach is one of the tourist destinations in Pacitan Regency which is being developed in the form of ecotourism through collaboration between stakeholders and strengthening their interactions. The number of visitors to Klayar Beach in the last 4 years has seen an increase and decrease in unstable tourists, but it is still the highest number of tourists in Pacitan Regency. This is inseparable from the management of the Klayar Panti which can attract tourist visits related to the aspects of offering 4A tourism products (attraction, amenities, accessibility, and ancillary). The purpose of this research is to describe and analyze the aspects of ecotourism product offerings at Klayar Beach. The approach used in this research is qualitative by using descriptive method. The data used in this study are primary data and secondary data, namely the results of interviews, observations, and documentation. The result of the research is that there is a tourist attraction which is an unspoiled natural resource with an ocean flute icon which is the hallmark of Klayar Beach. In terms of the amenities component of Klayar Beach, it seems that it has not met the needs of tourists due to the lack of adequate accommodation infrastructure development, such as hotels and restaurants that do not yet exist on Klayar Beach. Likewise, access to Klayar Beach can only be accessed by land travel, lack of transportation such as airports and ports, the last component that supports tourist activities, namely Klayar Beach, has been managed by the local government through the Pacitan DISPARBUDPORA in collaboration with POKDARWIS in Sendang Village. The supporting factors are in the attraction because there is an oceanic flute as an icon of Klayar Beach while the inhibiting factors are still not fulfilled from the aspects of amenities, ancillary and accessability.